The Relevance Of Al-Qur’an Principles In Improving The Quality Of Educational Facilities And Infrastructure - Loqman Rizani; Luvy Afrilianty; Mizatul Fazira; Syafaatul habib (Penerbit Hellow Pustaka, 2025)
Educational facilities and infrastructure have a very important role in supporting an effective and quality learning process. This article aims to present the results of research on the relationship between the principles of the Qur'an and efforts to improve the quality of educational facilities, as well as to evaluate and optimize their management in order to support the achievement of student quality. This research is based on the importance of increasing awareness of the role of educational facility management in encouraging the efficiency and effectiveness of the teaching and learning process. The method used is a literature study, which examines in depth the concept of educational facility and infrastructure management, its application according to the perspective of the Qur'an, its objectives, elements, and underlying principles. The research findings show that facility and infrastructure management is an essential component that cannot be separated from the education system.